Impact of bilingual education programs on limited English proficient students and their peers: Regression discontinuity evidence from Texas - Aimee Chin; N. Meltem Daysal; Scott A. Imberman (Institute for the Study of Labor (IZA), 2012)
Texas requires a school district to offer bilingual education when its enrollment of limited English proficient (LEP) students in a particular elementary grade and language is twenty or higher. Using school panel data, we find a significant increase in the probability that a district offers bilingual education above this 20-student cutoff. Using this discontinuity as an instrument for district bilingual education provision, we find that bilingual education programs do not significantly impact the standardized test scores of students with Spanish as their home language (comprised primarily of ever-LEP students). However, there are significant positive spillover effects to their non-LEP peers.
Keywords: I21; J24; 330; bilingual education; Studierende; Sprache; Bildungsniveau; Texas